Seguimiento farmacoterapéutico en pacientes con epilepsia en un hospital de Iquitos, 2023 - Rios Araujo, Felipe Franco (2024)
The research aims to improve pharmacotherapy and therapeutic adherence in patients with epilepsy, treated in the neurosurgery and neurology clinic of Hospital III- Iquitos, EsSalud 2023, the study methodology is quantitative, observational, descriptive, cross-sectional and prospective. The sample size is 30 patients, the pharmacotherapeutic monitoring sheet was applied, the Morisky Green test was applied to determine adherence to treatment, the results regarding sociodemographic characteristics, age from 18 to 26 years with 53,3%, sex male was 56,7%, origin from Iquitos 100% and single marital status was 56,7% respectively, the PRMs identified were PRM5 with 70,0% the most frequent and the effectiveness category with 53,3%. Likewise The Morisky Green test shows that 60,0% of patients adhere to treatment. It was concluded that pharmacotherapeutic monitoring contributes to adherence to pharmacological treatment in patients with epilepsy who were treated in the neurosurgery and neurology clinic of Hospital III-Iquitos, EsSalud, during the months of January to June 2023.